Systematization of experiences and construction of situated knowledge: the case of 'Del Monte - Alquimia Nativa' in the Social and Solidarity Economy of San Luis (La Rivada, 2025)
This article shares the experience of a Social Interest Extension Project (SEP) at the Universidad Nacional de San Luis (UNSL) developed with producers in the rural area of Villa de Merlo (San Luis, Argentina). This project, aimed at strengthening Social and Solidarity Economy (SSE) ventures from a communication perspective, focused on strengthening their identity. The starting point was the identification of a shared problem: the need to consolidate the identity of a local organization called "Del Monte. Alquimia Nativa" and improve its visibility and marketing strategies in a context marked by structural inequalities. The central objective was to support territorial strengthening processes and, simultaneously, systematize the experience as a tool for producing knowledge at the intersection of SSE and Communication.
Keywords: University Out reach; Social and Solidarity Economy; Communication; Systematization of experiences